Digital Technology Approach in Scientific Writing: Artificial Intelligence Training for Teachers and Students - Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Ady Kurnia; Arif Ridha (Jurnal Pengabdian UNDIKMA, 2026)
This study aims to improve the scientific writing skills of teachers and students through the utilization of artificial intelligence (AI) technology. The community service program employed two main approaches, namely knowledge sharing and participatory learning, which included lectures, hands-on training, group discussions, case studies, and practical exercises on the use of AI tools for scientific writing. The results demonstrated improvements in participants' scientific writing skills, enhanced understanding of AI concepts, and greater proficiency in applying AI technology throughout the writing process. Furthermore, the program improved the quality of scientific writing, increased participants' interest and confidence in producing scientific papers, and promoted the effective integration of AI technology into academic writing practices. Overall, this community service program contributes positively to the development of scientific writing competencies among teachers and students.